History of actions that deconstruct the hybrid teaching modality at the secondary level - Domínguez Galván, Claudia Ibete (2026)
Secondary education is the final level of basic education in Mexico. In its face-to-face format, this level of education faces disruptions to school activities from both internal and external sources, which jeopardize the initiation, continuation, and completion of students' academic paths. The objective of this study was to analyze official actions, strictly related to the beginning of the formalization/evolution of technology (1865) and the first to the most recent program that introduced technology—other than printed materials—in secondary education (2011), through a documentary analysis. The aim was to identify elements that could contribute to proposing a hybrid teaching model for the selected educational level. The study was conducted using a qualitative/exploratory methodology with a deconstructivist approach, which allowed for the identification of 33 actions that reflect the formalization/evolution and the sum of other concepts, as well as the different moments in which various technologies were integrated into classrooms. It is known that these actions generated programs that have been limited to pilot programs, have been temporary, and have had limited coverage. It was concluded that the actions analyzed are biased by the following duality: on the one hand, they strengthen, diversify and attempt to modernize it, and on the other hand, they contain marginal phenomena such as the lack of planning, monitoring, evaluation and continuity.